Workspace - Unknown:::Creator::::::::::::
Negative shows a workspace with a slide projector, a briefcase with film laying loose on top of other items, and several different sized boxes sitting randomly on it's desktop. Some of the boxes are open. There are shelves on the walls that are empty except for one small unidentified item.